Morphoanatomy of three Indigofera species (Leguminosae-Papilionoideae) in Java, Indonesia - Henta Fugarasti; Muzzazinah MUZZAZINAH; Murni Ramli (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fugarasti H, Muzzazinah, Ramli M. 2020. Morphoanatomy of three Indigofera species (Leguminosae-Papilionoideae) in Java Indonesia. Biodiversitas 21: 5531-5538. This study aimed to explore the morphological and detailed anatomical features of the stems, leaves, and roots from three Indonesian Indigofera species. Morphological-anatomical studies of three Indonesian Indigofera species were carried out using embedded microscopic preparations. The anatomical characters of the specimens were observed using a compound optical microscope with magnification 40x, 100x, and 400x. The observation showed the anatomical cross-section of  I. tinctoria stem was rectangular, I. suffruticosa was hexagonal, and I. arrecta was rounded. The tissue structures of Indigofera species, from the outside layer, were the epidermis, thin cortex, secondary phloem (narrow or wide), thick secondary xylem, and conspicuous pith in the middle. Whilst, the corner of I. suffruticosa stem contained thick collenchyma. The vascular bundles were the open collateral. The leaves of Indigofera species are made up of the upper epidermis, mesophyll (palisade parenchyma, spongy parenchyma), and the lower epidermis. The vascular bundles were located in the middle, with five or six segments of the xylem elements and small groups of phloem elements, all in the parallel lines. The primary stele type of the roots is actinostele, cambium activity pushed him aside. The vascular bundle of the roots consisted of a dense and tight secondary xylem composed of thick-walled circular vessels (mostly tightly arranged). Data about the morphoanatomy structure of three Indonesian Indigofera species could complement the novelty of the morpho-anatomy information records obtained by previous researchers.